Thrombolysis for Intraventricular Hemorrhage - Wong, Ricky H.; Bailes, Julian E. (Seminars in Thrombosis and Hemostasis, 2013)
Intraventricular hemorrhage is a frequent complication of intracerebral hemorrhage and is independently associated with significant morbidity and mortality. Intraventricular fibrinolytic therapy is used with increasing frequency to accelerate clot clearance. We review the recent evidence and discuss the therapeutic benefits as well as the current concerns and limitations of fibrinolytic use in this setting.
Keywords: intraventricular hemorrhage; intracerebral hemorrhage; fibrinolytics; tissue plasminogen activator